Mechanocombinatorially screening sensitivity of stretchable strain sensors - Pan, Shaowu (2020)
Stretchable strain sensors have aroused great interest for their application in human activity recognition, health monitoring, and soft robotics. For various scenarios involving the application of different strain ranges, specific sensitivities need to be developed, due to a trade‐off between sensor sensitivity and stretchability. Traditional stretchable strain sensors are developed based on conductive sensing materials and still lack the function of customizable sensitivity. A novel strategy of mechanocombinatorics is proposed to screen the sensor sensitivity based on mechanically heterogeneous substrates. Strain redistribution over substrates is optimized by mechanics and structure parameters, which gives rise to customizable sensitivity. As a proof of concept, a local illumination method is used to fabricate heterogeneous substrates with customizable mechanics and structure parameters. A library of mechanocombinatorial strain sensors is created for extracting the specific sensitivity. Thus, not only is an effective strategy for screening of sensor sensitivity demonstrated, but a contribution to the mechanocombinatorial strategy for personalized stretchable electronics is also made.